The politics of public education reform ideas and issues - Gunter, Helen ca. 20./21. Jh (Policy Press, 2018)
This book critically examines the key issues facing the public with implications for education policy makers, professionals and researchers, confronting current issues about social justice and segregation. The author uses Arendtian ideas to help the reader to 'think politically' about education and how public services education can be reimagined